Photonic device design of cutting-edge silicon photonics technology via state-of-the-art commercial software - Muhammad Aizat Zainuddin (2019)
Through Moore’s law, it has been observed that, in every two years, the number of transistors in a dense integrated circuit (IC) doubles. However, due to the breakdown of Dennard scaling, in which increasing clock frequencies does not improve performance of ICs anymore despite Moore’s law, we have reached the point where electrical interconnects have become the limiting factor in our goal to achieve higher computational speeds. Photonic integrated circuits (PIC) have been shown to be a promising solution to this problem. This done by using optical interconnects instead of electrical ones. However, this has not come to fruition due to the fact that an efficient laser source on silicon has not been created yet. So far, the creation of a practical on-chip laser using Si-compatible group IV semiconductor materials has been close to impossible due to their indirect band-gap nature.